Wi-Fi Optimization with Wireless Mesh Networks - Arya, Primadona; Febriyan Priambodo, Dimas (Media of Computer Science, 2024)
Wifi is one technology that can still penetrate into several services around us. The need for additional services in the form of our wifi trigger to provide solutions to improve quality, security and even coverage. By using an ordinary single access point, the wifi performance is not optimal because of the interference between signals and the strength or in between with wifi repeater. Access point need more power to extend range. With a mesh network, the performance of the access point can be maximized. This research shows that mesh implementation can increase from -20dB bellows to above -50dB or more than 100%. With mesh network wifi can be seen in single SSID different with repeater that has own coverage and setting. Mesh network connecting all client seamless to near node in single network SSID.